2014
DOI: 10.1016/j.molcel.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

IRAK4 Dimerization and trans -Autophosphorylation Are Induced by Myddosome Assembly

Abstract: SUMMARY Trans -autophosphorylation is among the most prevalent means of protein kinase activation, yet its molecular basis is poorly defined. In Toll-like receptor and interleukin-1 receptor signaling pathways, the kinase IRAK4 is recruited to the membrane proximal adapter MyD88 through death domain (DD) interactions, forming the oligomeric Myddosome and mediating NF-κB activation. Here we show that unphosphorylated IRAK4 dimerizes in solution with a Kd of 2.5 μM and that Myddosome assembly greatly enhances IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
161
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(168 citation statements)
references
References 41 publications
7
161
0
Order By: Relevance
“…On the other hand, oligomerization of effector enzymes, such as kinases and caspases, enhances the allosteric changes that are presumed to be required for enzyme activation. This oligomerization-facilitated allostery is illustrated by the recently reported crystal structure of the unphosphorylated IRAK4 kinase domain asymmetric dimer captured in the conformation of the Myddosome-induced IRAK4 trans -autophosphorylation reaction 34 . In the crystal structure, one IRAK4 monomer exists in the active kinase conformation despite a lack of phosphorylation and it precisely binds the activation loop phosphosite of the other IRAK4 monomer for phospho-transfer.…”
Section: Smocs For Prrsmentioning
confidence: 90%
“…On the other hand, oligomerization of effector enzymes, such as kinases and caspases, enhances the allosteric changes that are presumed to be required for enzyme activation. This oligomerization-facilitated allostery is illustrated by the recently reported crystal structure of the unphosphorylated IRAK4 kinase domain asymmetric dimer captured in the conformation of the Myddosome-induced IRAK4 trans -autophosphorylation reaction 34 . In the crystal structure, one IRAK4 monomer exists in the active kinase conformation despite a lack of phosphorylation and it precisely binds the activation loop phosphosite of the other IRAK4 monomer for phospho-transfer.…”
Section: Smocs For Prrsmentioning
confidence: 90%
“…Oligomerization-induced autophosphorylation of IRAK4 must execute through allosteric changes that are only possible at a high local concentration. The recent crystal structure of the IRAK4 kinase domain (KD) containing an active site mutation showed an asymmetric dimer structure caught in the act of trans -autophosphorylation (54). Despite being unphosphorylated, one IRAK4 KD molecule (the “enzyme”) is in the active conformation, whereas the other IRAK4 KD molecule (“substrate”) shows a protruded activation loop.…”
Section: The Toll-like Receptor/il-1r Signaling Pathwaymentioning
confidence: 99%
“…The enzyme IRAK4 active site precisely accepts the cognate phosphorylation residue T345 from the substrate for trans -autophosphorylation (Figure 3 f ). Further biochemical and cellular studies show that the observed dimerization interface is vital for IRAK4 autophosphorylation and signal transduction (54). Small- and wide-angle X-ray scattering (SAXS/WAXS) of full-length (FL) IRAK4 in complex with MyD88 DD reveals a central core with two flanking lobes, suggesting a MyD88/IRAK4 DD complex core at the center and two IRAK4 KD dimers at the periphery (Figure 3 g ).…”
Section: The Toll-like Receptor/il-1r Signaling Pathwaymentioning
confidence: 99%
“…Several kinase structures have been reported in which a serine, threonine, or tyrosine autophosphorylation site of one kinase monomer is present in the active site of another monomer of the same protein in the crystal (7-15). In these structures, the position of the phosphorylation site and adjacent residues resembles those of substrates in structures of substrate peptides bound to kinases (16-18).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, each of these residues is an experimentally verified autophosphorylation site in these kinases. For serine/threonine kinases, autophosphorylation complexes of the activation loop Thr residues of p21-activated kinase (PAK1) [PDB: 3Q4Z (11)] and interleukin-1 receptor-associated kinase 4 (IRAK4) [PDB: 4U97; PDB: 4U9A (15)] have been described, as have autophosphorylation complexes of the C-terminal regulatory regions of human [PDB: 2WEL (12)] and Caenorhabditis elegans [PDB: 3KK8; PDB: 3KK9 (13)] calcium/calmodulin-dependent kinase II (CaMKII).…”
Section: Introductionmentioning
confidence: 99%